2021
DOI: 10.3390/s21051584
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Energy Assessment Training Effectiveness Evaluation: An Eye-Tracking Study

Abstract: It is essential to understand the effectiveness of any training program so it can be improved accordingly. Various studies have applied standard metrics for the evaluation of visual behavior to recognize the areas of interest that attract individuals’ attention as there is a high correlation between attentional behavior and where one is focusing on. However, through reviewing the literature, we believe that studies that applied eye-tracking technologies for training purposes are still limited, especially in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…This is contrary to other studies [4,14,15]. Waite [38] found that surface damages are easier to find on green painted composite panels. In the present study, the green background colour showed the highest positive-rate (TP & FP) and was significantly higher compared to the white background, F(3, 796) = 2.315, p < 0.05.…”
Section: H5contrasting
confidence: 68%
“…This is contrary to other studies [4,14,15]. Waite [38] found that surface damages are easier to find on green painted composite panels. In the present study, the green background colour showed the highest positive-rate (TP & FP) and was significantly higher compared to the white background, F(3, 796) = 2.315, p < 0.05.…”
Section: H5contrasting
confidence: 68%
“…The exit survey showed that most participants found the inspection of dirty blades more challenging. This is backed up by the general literature that agrees that an increase in fixation parameters implies a higher task complexity and cognitive load [ 64 , 114 , 119 , 120 , 121 , 122 , 123 , 124 ].…”
Section: Discussionmentioning
confidence: 89%
“…Again, this was a time-consuming and onerous task, showing that even automatically generated time marks required manual adjustment. While it was relatively simple to exclude the relevant gaze plots in our study (due to the plain background), it would have been more challenging in situations where the stimuli showed complex environments, such as the ones shown in [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that eye tracking technology offers an unbiased evaluation of visual search behavior, it is not unexpected that the application of this technology in construction safety studies has grown recently (e.g. [33][34][35][36][37]). For example, Li et al [35] aimed to identify the mental fatigue level of the operators by using eye-tracking technology through a virtual excavation simulation.…”
Section: Eye-tracking For Construction Safetymentioning
confidence: 99%